Etika Komunikasi dalam Perspektif Al Qur’an Qs. Ar-Rahman - Fuadul Mustofa; Sigit Purnama (Departement of Mathematics Education, 2024)
Ethics is morals, while communication in the Qur’an means that humans are given instructions by Allah SWT to communicate well so that they can explain the meaning of something. The aim of this research is to dig deeper into the meaning contained in Surah Ar-Rahman verses 1-4 according to the views of Ibnu Katsir and Al Misbah. The research method used is the library research method using an interpretive approach (Ibnu Katsir and Al-Misbah). The data sources used are primary data sources and secondary data sources. The results of the discussion in the Al-Qur’an Surah Ar-Rahman verses 1-4 in both commentaries, namely Ibn Kathir and Al Misbah, are that both discuss the meaning of Bayan. In Ibn Kathir’s Tafsir, the meaning of Bayan means speaking. Because siyaq is in the teaching of the Koran by Allah Ta’ala, namely how to read it. And this happens by making it easier to pronounce the articulation, as well as making it easier for the letters to come out through their respective paths from the throat, tongue and two lips according to the variety of articulations and types of letters. Meanwhile, the meaning of Bayan in Tafsir Al-Misbah Al-Bayan Teaching is not only limited to speech, but includes all forms of expression, including art and facial expressions. In fact, according to Al-Biqa’I, the word Al-Bayan is the potential for thinking, namely knowing kulli and juz’I issues, assessing the visible and also the unseen and making an analogy with the visible. Once with signs, another time with calculations, a third time with predictions and the next time with looking at the universe and other ways, while distinguishing between good and bad or something like that. This all carries with it the potential to decipher something hidden and explain and teach it to others. Once with words, other times with deeds, with speech, writing, gestures, etc. In this way, humans are able to perfect themselves and at the same time perfect others.